Christobiography: memory, history, and the reliability of the Gospels - Keener, Craig S. (Eerdmans Publishing Co, 2019)
"The canonical gospels are ancient biographies, narratives of Jesus's life. The authors of these gospels were intentional in how they handled historical information and sources. Building on recent work in the study of ancient biographies, Craig Keener argues that the writers of the canonical gospels followed the literary practices of other biographers in their day. In Christobiography he explores the character of ancient biography and urges students and scholars to appreciate the gospel writers' method and degree of accuracy in recounting the ministry of Jesus. Keener's Christobiography has far-reaching implications for the study of the canonical gospels and historical-Jesus research. He concludes that the four canonical Gospels are historically reliable ancient biographies."--Dust jacket